2006
DOI: 10.1007/s00426-006-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

Input monitoring and response selection as components of executive control in pro-saccades and anti-saccades

Abstract: Several studies have shown that antisaccades, more than prosaccades, are executed under executive control. It is argued that executive control subsumes a variety of controlled processes. The present study tested whether some of these underlying processes are involved in the execution of antisaccades. An experiment is reported in which two such processes were parametrically varied, namely input monitoring and response selection. This resulted in four selective interference conditions obtained by factorially com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…executive processes are involved only at an earlier point, in constructing the task set or in choosing one to be retrieved from long-term memory. Thus, my conceptualization of executive functions differs in one respect from that of Vandierendonck and colleagues (Szmalec et al, 2005;Vandierendonck, Deschuyteneer et al, 2008) because I regard response selection as a basic process, not an executive process.…”
Section: Executive Functionsmentioning
confidence: 89%
See 2 more Smart Citations
“…executive processes are involved only at an earlier point, in constructing the task set or in choosing one to be retrieved from long-term memory. Thus, my conceptualization of executive functions differs in one respect from that of Vandierendonck and colleagues (Szmalec et al, 2005;Vandierendonck, Deschuyteneer et al, 2008) because I regard response selection as a basic process, not an executive process.…”
Section: Executive Functionsmentioning
confidence: 89%
“…Inspired by the work of baddeley (1986), the processing side of working memory is often conceptualized as a "central executive" or, more recently, as a bunch of executive processes. However, as Vandierendonck, Deschuyteneer, Depoorter, and Drieghe (2008) have noted, the term "executive processes" remains vague, and no consensus has yet emerged on what belongs to the set of executive processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar design, Evens and Ludwig (2010) reported data on the simultaneous execution of antisaccades (i.e., saccades directed away from a transient in the periphery) during a perceptual task which involved the detection of a luminance change. Dual-task costs in terms of increased saccade RTs were observed, which were attributed to a general increase in the response criterion for saccade generation in dual-task conditions (see also Roberts, Hager, & Heron, 1994;Stuyven, Van der Goten, Vandierendonck, Claeys, & Crevits, 2000;Vandierendonck, Deschuyteneer, Depoorter, & Drieghe, 2008). Another study reported worse performance in a number processing task during the simultaneous execution of saccades (Irwin & Thomas, 2007).…”
Section: Interference Between Saccades and Manual Responses: Implicatmentioning
confidence: 90%
“…Such a conceptualisation has many drawbacks, not in the least that it is a homunculus (e.g., Baddeley, 1996). Several attempts have been made to fractionate the central executive, by looking into separate executive functions (e.g., Burgess, 1997;Miyake, Friedman, Emerson, Witzki, Howerter, & Wager, 2000), or by looking into even simpler executive control processes required to cope with task demands (e.g., Vandierendonck, Szmalec, Deschuyteneer, & Depoorter, 2007), such as input and output monitoring (e.g., Deschuyteneer & Vandierendonck, 2005a;Vandierendonck, Deschuyteneer, Depoorter, & Drieghe, 2008), response selection (e.g., Deschuyteneer & Vandierendonck, 2005b;Szmalec, Vandierendonck, & Kemps, 2005), memory updating (e.g., Kane, Conway, Miura, & Colflesh, 2007;Szmalec, Verbruggen, Vandierendonck, & Kemps, 2011), and inhibition (e.g., Friedman & Miyake, 2004;Verbruggen & Logan, 2008).…”
Section: Introductionmentioning
confidence: 99%